Do Emotions Benefit Investment Decisions? Anticipatory Emotion and Investment Decisions in Non-professional Investors - Hinvest, Neal S.; Alsharman, Muhamed; Roell, Margot; Fairchild, Richard (Frontiers in Psychology, 2021)
Increasing financial trading performance is big business. A lingering question within academia and industry concerns whether emotions improve or degrade trading performance. In this study, thirty participants distributed hypothetical wealth between a share (a risk) and the bank (paying a small, sure, gain) within four trading games. Skin Conductance Response (SCR) was measured while playing the games to measure anticipatory emotion, a covert emotion signal that impacts upon decision-making. Anticipatory emotion was significantly associated with trading performance but the direction of the correlation was dependent upon the share’s movement. Thus, anticipatory emotion is neither wholly “good” nor “bad” for trading; instead, the relationship is context-dependent. This is one of the first studies exploring the association between anticipatory emotion and trading behaviour using trading games within an experimentally rigorous environment. Our findings elucidate the relationship between anticipatory emotion and financial decision-making and have applications for improving trading performance in novice and expert traders.